Peningkatan Hasil Belajar Bahasa Arab Peserta Didik Melalui Penerapan Teknik Think, Pair, Share Di Taman Tahfidz Ar-Rahman Gunung Sindur Bogor - Muhammad Dhiya; Siskha Putri Sayekti (Al Makki Publisher, 2023)
The purpose of this study was to determine the improvement of Arabic language learning outcomes by applying the Think, Pair, Share (TPS) technique. This research is a type of classroom action research with the Kemmis & McTaggart model. The research subject which is the source of data collection is Ar-Rahman Tahfidz Park in Gunung Sindur, Bogor Regency. The results showed two things; (1) there was no significant increase in the use of the TPS technique with learning outcomes; (2) despite the insignificance, there were learning outcomes that increased with the continuous use of the TPS technique.